Ethnic-racial relations in the training of teachers of a quilombola school - Freitas, Michelle Gomes; Eugenio, Benedito (Revista Hipótese, 2020)
This text presents the results of the research that aimed to identify the presence and / or absence of ethnic-racial issues in the formative trajectories of teachers who work in a school institution inserted in a quilombola context. The methodology used was qualitative and counted on the use of a questionnaire to produce the data. We analyze the knowledge about the ethnic-racial relations of the teaching staff of the initial years of elementary school in a quilombola school. The conclusions point to the monocultural character of the researched school.
Keywords: Ethnic-racial relations; Quilombola school; Knowledge of teachers